An Analysis of The Application PPP (Presentation, Practice and Production) Method on Descriptive Text Material in Seventh Grade Students SMPN 1 Moyo Utara - Khairun Nisa Islami; Ade Dwi Ahyanti (Universitas Islam Tribakti Lirboyo Kediri, 2025)
English is a second language that must be introduced to children from an early age to support children's education and development in the global era. In accordance with the level of English education, it has been determined as a subject. This starts from elementary school, middle school to high school. Appropriate teaching methods in the teaching and learning process can make the student learning process more enjoyable. To deliver the material well, of course the teacher choose the right method to help improve student development. This research aimed to discover the difficulties and the advantages that the teacher faced during applying PPP method in English learning. The study employed a qualitative descriptive method and was conducted at SMPN 1 Moyo Utara, involving seventh-grade students and one English teacher.